Migrant society, Intercultural Identity and Education - Pastena, Nicolina (Formazione & insegnamento, 2017)
Italy, as well as other European Countries, is now destination of many migration flows. This situation creates several political, economic, social and cultural problems. A new concept of society is growing up, not tied to local culture circumscribed stereotypes, but open to multiple ways explanatory; an interacting society that takes on a new dimension, which we might call “migrant society”. The idea of a migrant society and the complex dynamics of cultural interactions, requires a new way of thinking about the educational processes, a new teaching strategy that can synergistically intersect with various and different cultural approaches.